Core Cross-Linked Block Ionomer Micelles as pH-Responsive Carriers for cis-Diamminedichloroplatinum(II) - Oberoi, Hardeep S. (2011)
Benefits of the frequently prescribed platinum (II) chemotherapy drugs are compromised by undesirable side effects, poor pharmacokinetics and development of drug resistance. Polymer micelles derived from amphiphillic block copolymers, offer a novel macromolecular platform for carrier based delivery of such compounds. Soft polymeric nanocarriers were synthesized by template-assisted method involving condensation of the poly(ethylene oxide)-b-polymethacrylate anions by metal ions into core-shell block ionomer complex micelles followed by chemical cross-linking of the polyion chains in the micelle cores. The resulting micelles can efficiently incorporate cisplatin with a high loading capacity (up to 42 %w/w). Core cross-linking stabilized the micelles against structural disintegration and prevented premature drug release. The reversible cisplatin entrapment involved the carboxylate groups of the micellar core. The drug was released in a pH- responsive manner, without loss of its biological activity. The stable cross-linked polymer micelles can potentially improve platinum (II) drug disposition with improved therapeutic potential.